Encapsulation of a [Dy(OH2)(8)](3+) cation: magneto-optical and theoretical studies of a caged, emissive SMM - Al Hareri, M.
The first supramolecular cage formed by three benzo-15-crown-5 macrocycles encapsulating a [Dy(OH2)(8)](3+) guest cation is reported, with the Dy(III) centre exhibiting local pseudo square antiprismatic D-4d symmetry. The anisotropy barrier extracted from ac susceptibility studies, emission spectroscopy and ab initio calculations reveals that the second excited state Kramers doublet plays a key role in the magnetization dynamics due to the Ising character and near coparallel nature of the ground and first excited Kramers doublets.